Temporal Patterns of Methane Emissions From Two Streams With Different Riparian Connectivity. Issue 8 (11th August 2021) - Leng, Peifang; Kamjunke, Norbert; Li, Fadong; Koschorreck, Matthias
Abstract: Streams are regionally important sources of CH4 to the atmosphere, but the temporal variability in and control on CH4 concentrations and emissions are not well understood. Especially, lack of long‐term data hampers our ability to predict CH4 emissions from streams. Here, we present a 7‐year data set of biweekly CH4 concentration and underlying potential drivers from two adjacent small German streams with contrasting riparian area characteristics. Over the 7‐year study period, mean CH4 concentration and emissions were 0.20 and 0.07 μmol L −1 and 2.01 and 0.84 mmol m −2 d −1 for the two streams, respectively. Our findings suggest that the combination of seasonality and topography ultimately shaped the considerable temporal variations of CH4 . CH4 oxidation and production in the streams were probably of minor importance. Instead, fluctuations in CH4 concentrations likely reflected a temporal pattern of CH4 input from soils of the riparian zone with larger CH4 variations in the stream with more riparian lands. Structural equation modeling revealed dissolved organic carbon and nitrate as important predictors of CH4 concentration. However, we did not identify predictors of the considerable short‐term variability, nor the explicit pathways of CH4 delivery to streams. The discrepancy of the CH4 flux between streams was likely triggered by different connectivities to riparian soils with higher CH4 emissions in the hydrologically more connected stream. Interannual comparison showed that changing hydrologic conditions, rather than warming, may impact future CH4 emissions from temperate streams. We predict that higher CH4 emissions occur in wetter years in streams with close connectivity to riparian soils. Plain Language Summary: Streams are increasingly recognized as an important source of methane (CH4 ) to the atmosphere. However, emissions are extremely variable because the CH4 concentration in streams changes a lot with time. We analyzed a long‐term time series of CH4 concentrations in two small German streams to understand the mechanisms behind these temporal fluctuations. Our two streams were always supersaturated in CH4 and thus, emitted CH4 to the atmosphere. A large part of the temporal variability can be explained by seasonal changes of discharge and temperature. However, CH4 was also highly variable on a biweekly timescale, even under a constant low discharge, which we cannot explain. Whereas the temporal pattern was similar in the two streams, fluxes were higher and more variable in the stream with a shallower valley and, accordingly, a better connection to floodplain soils. Climate change will probably increase stream temperature and change annual precipitation. We predict that annual CH4 emissions will increase during wetter years in streams with a close connection to their floodplains, and that this effect will be more important than a temperature rise. Key Points: CH4 evasion has considerable temporal variations primarily due to seasonal changes in discharge and temperature Riparian connectivity modulates the temporal response of CH4 emissions